2016
DOI: 10.1128/genomea.00646-16
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Campylobacter iguaniorum Strain RM11343, Isolated from an Alpaca

Abstract: Campylobacter iguaniorum is a member of the C. fetus group of campylobacters and is one of two Campylobacter taxa isolated from reptiles. This study describes the whole-genome sequence of the C. iguaniorum strain RM11343, which was isolated from a California alpaca fecal sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…To clarify the taxonomic structure of the C. fetus group and further characterize these putative novel taxa, the genomes of five strains, including the C. lanienae type strain NCTC 13004 and representatives of all three putative novel taxa, were sequenced to completion; additional genomes were sequenced to draft level. The genomes of all other described taxa within the C. fetus group have been sequenced to completion ( Gilbert et al 2013 , 2014 ; Miller et al 2016a , 2016b ; Oliveira et al 2016 ; Stynen et al 2011 ; van der Graaf-van Bloois et al 2014a , 2014b ); thus, a full comparative genomic analysis of the C. fetus group could be accomplished with the new genomic data.…”
Section: Introductionmentioning
confidence: 99%
“…To clarify the taxonomic structure of the C. fetus group and further characterize these putative novel taxa, the genomes of five strains, including the C. lanienae type strain NCTC 13004 and representatives of all three putative novel taxa, were sequenced to completion; additional genomes were sequenced to draft level. The genomes of all other described taxa within the C. fetus group have been sequenced to completion ( Gilbert et al 2013 , 2014 ; Miller et al 2016a , 2016b ; Oliveira et al 2016 ; Stynen et al 2011 ; van der Graaf-van Bloois et al 2014a , 2014b ); thus, a full comparative genomic analysis of the C. fetus group could be accomplished with the new genomic data.…”
Section: Introductionmentioning
confidence: 99%
“…hyointestinalis DSM 19053 1 CR67_01870 Porcine intestine SAMN01176354 @ C. hyointestinalis ssp. lawsonii CCUG 27631 1 CHL_RS06765 Porcine intestine [ 37 ] C. iguaniorum RM11343 1 CIG11343_RS03950 Alpaca faeces [ 21 ] a Genome online database project ID. @ NCBI Biosample ID …”
Section: Resultsmentioning
confidence: 99%
“…In addition to C. concisus , a number of other Campylobacter species were recently reported to have the zot genes [ 17 21 ]. In this study, we found that Campylobacter zot genes formed two clusters (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported overall prevalence in reptiles based on culturing was 8.2%; 15.6% of the chelonians and 6.1% of the lizards, but none of the snakes examined, carried this Campylobacter species ( Gilbert et al 2014a ). Recently, Cig has also been isolated from a non-reptilian host ( Miller et al 2016a ).…”
Section: Introductionmentioning
confidence: 99%